How well does a wellbeing measure predict psychiatric 'caseness' as well as suicide risk and self-harm in adolescents?. (October 2018) - Parker, Gordon; Smith, Isabelle Granville; Paterson, Amelia; Romano, Mia; Hadzi-Pavlovic, Dusan; Ricciardi, Tahlia
Highlights: Low wellbeing scores may indicate psychiatric illness or suicidality. No meaningful wellbeing cut-off score was found to identify psychiatric disorders. The SWLS may complement measures of psychiatric diagnosis and suicidality. Abstract: Screening for psychiatric disorders may be hampered by traditional measures that increase participant burden and elicit negative responses via denial and social desirability biases. This study examined the utility of a wellbeing measure to identify psychopathology and suicide risk in adolescent participants. 1, 579 students from Sydney schools participated in a survey which assessed wellbeing using the Satisfaction With Life Scale (SWLS) as well as psychiatric disorders and suicide risk. Results showed that low scores on the SWLS discriminated adolescents who had experienced a psychiatric condition or suicidality from those not so assigned. Specifically, students with no psychiatric diagnosis yielded a mean SWLS score of 28.0 while for those assigned a diagnosis, mean scores ranged from 19.4–3.0 across the various psychiatric conditions. Students who reported any suicidal ideation yielded a mean SWLS score of 22.7, and those with a current suicidal plan yielded a mean score of 17.7. We derived SWLS cut-off scores for predicting psychiatric caseness and suicidality but established that they had low positive predictive power. The SWLS therefore appears to provide a limited proxy measure of the chance of a psychiatric disorder or psychological distress, and might usefully complement more direct measures of such states.